2010
DOI: 10.1590/s1516-89132010000100015
|View full text |Cite
|
Sign up to set email alerts
|

Cladia aggregata (lichen) from Brazilian northeast: chemical characterization and antimicrobial activity

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Besides that, the bacteria strains are also different between this investigation and Yilmaz et al [23]. Martins et al [25] reported MIC values of 50-100 µg/mL for (2) against various strains of S. aureus which is similar to this study where we obtained MIC value of 62.50 µg/mL concentration. Disk diffusion method has its own disadvantages where zone sizes are affected by the media used and by the different growth rates of organisms being tested therefore MIC tests are more accurate with anaerobic bacteria [26].…”
Section: Notes: a Acetone Extract; M Methanol Extractsupporting
confidence: 83%
“…Besides that, the bacteria strains are also different between this investigation and Yilmaz et al [23]. Martins et al [25] reported MIC values of 50-100 µg/mL for (2) against various strains of S. aureus which is similar to this study where we obtained MIC value of 62.50 µg/mL concentration. Disk diffusion method has its own disadvantages where zone sizes are affected by the media used and by the different growth rates of organisms being tested therefore MIC tests are more accurate with anaerobic bacteria [26].…”
Section: Notes: a Acetone Extract; M Methanol Extractsupporting
confidence: 83%
“…; it can be conceived that the Cladia extract will also be effective against other anthropophilic and zoophilic spp., namely, M. pachydermatis, M. japonica, M. yamatoensis and M. equii. The C. aggregata , along with Usnea baileyi and Everniastrum nepalense , has been found active against multidrug resistant Staphylococcus aureus [31, 32]. Established results on the antifungal activity of Everniastrum cirrhatum with minimum fungicidal concentration (MFC) of as low as 60  μ L/mL against human pathogenic fungi (dermatophytes), namely, Epidermophyton floccosum, Microsporum gypseum, M. canis, M. audounii, Trichophyton rubrum, T. mentagrophytes, T. violaceum, and T. tonsurans, have also been reported in the past [33].…”
Section: Resultsmentioning
confidence: 99%
“…Ribeiro et al (2006) also reported action of ether extract from C. substellata against human and plant pathogenic bacteria and supposed a synergic action between their components. Martins et al (2010) also showed a synergic action of organic extract of C. aggregata against S. aureus. Similar results about the synergism between lichen substances have been observed for ether extract of Heterodermia leucomela, that contained high content of ATR and zeorin as an accessory substance, against B. subtilis (Falcã o et al, 2002).…”
Section: In Vitro Antioxidant and Antimicrobial Properties Of Organicmentioning
confidence: 87%